Analysis of science learning outcomes on motion and force topics among seventh-grade students from gender perspective - Dian Nugraheni; Aisyah Az-Zahro; Agung Mulyo Setiawan; Erni Yulianti; Isnanik Juni Fitriyah; Fatimah Az-Zahro (Research and Development in Education (RaDEn), 2025)
Science education is crucial for equipping students with problem-solving skills in the 21st century. However, students' understanding of science material, particularly motion and force, often varies and impacts learning outcomes. This study aims to analyze the science learning outcomes for motion and force material among seventh-grade MTs students and to investigate whether there are significant differences based on gender. This research employed a mixed-methods approach with a sequential explanatory design, involving 77 seventh-grade students from 2 male and 2 female classes. Data were collected using a test instrument (12 two-tier multiple-choice questions, C3-C5 cognitive levels), questionnaires, and teacher interviews. Quantitative descriptive and inferential data analyses (independent samples t-test) were conducted after normality and homogeneity tests. The findings reveal a significant difference in science learning outcomes for motion and force material between male and female students. The average learning outcome for female students (66.46) was higher than that for male students (56.62). This difference was consistent across cognitive indicators (application, analysis, evaluation) and sub-materials (motion and force). Observations indicated that female students demonstrated higher ambition and logical prioritization, aligning with the finding that they consistently achieved better scores.